Characterization of hello message exchange to estimate sensor node's neighborhood residual energy distribution in initialization phase. Issue 7 (28th April 2011) - Fang, Shudong; Berber, Stevan Mirko; Swain, Akshya Kumar
ABSTRACT The paper characterizes the hello message exchange (HME) procedure for a sensor node to develop its neighborhood residual energy distribution in the initialization phase of a static wireless sensor network. Because of the lack of coordination on channel access in the initialization phase, hello messages from multiple nodes face a high risk of data collision in the exchange course. A discovery ratio is hereby defined to measure the sufficiency of the HME procedure. The discovery ratio is related to the precision of the parameter estimates for the probability density function of a node's neighborhood residual energy distribution. To achieve an arbitrarily high discovery ratio within a resolvable time interval, the HME procedure is implemented using Birthday protocol, which results in large node energy consumption. To overcome this flaw, a method termed carrier sensing mini‐slot algorithm is proposed to carry out the HME procedure. The time duration and the node energy consumption for the HME procedures based on the Birthday protocol and the carrier sensing mini‐slot algorithm, respectively, are theoretically analyzed and verified by simulations. Copyright © 2011 John Wiley & Sons, Ltd.